2022
DOI: 10.2340/17453674.2022.2460
|View full text |Cite
|
Sign up to set email alerts
|

Stress fractures of the femoral neck in adults: an observational study on epidemiology, treatment, and reoperations from the Swedish Fracture Register

Abstract: Background and purpose: Stress fractures of the femoral neck (sFNFs) are uncommon injuries. Studies on sFNFs are rare. We describe the demographics, classification, treatment, reoperation rates, and mortality in a cohort of sFNF patients from the Swedish Fracture Register (SFR). Patients and methods: We included 146 patients ≥ 18 years of age with an sFNF registered in the SFR between 2011 and 2020. The cohort was linked with the Swedish Arthroplasty Register and reviewed using medical records and radiographs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Incidence rates in traumatic versus stress fractures may differ due to differences in surrounding tissue damage from trauma and differences in patient characteristics. Furthermore, risk of avascular necrosis and nonunion is not completely eliminated with internal fixation and fixation failure can occur [18]. Two relatively large retrospective MRI studies have identified prognostic fracture characteristics that may help guide the surgeon in choice of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incidence rates in traumatic versus stress fractures may differ due to differences in surrounding tissue damage from trauma and differences in patient characteristics. Furthermore, risk of avascular necrosis and nonunion is not completely eliminated with internal fixation and fixation failure can occur [18]. Two relatively large retrospective MRI studies have identified prognostic fracture characteristics that may help guide the surgeon in choice of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of sFNFs has been found to be 100/100.000 personyears in a military population, while bilateral sFNFs are much rarer and not presented by an incident rate in the literature. Available literature largely focuses on athletes and military personnel [1][2][3][4][5][6][7][8][9][10][11][12][13] as protentional candidate for SFNF. Prospective series show that 8% of stress fractures in competitive track and field athletes are located in the femur and 5% of stress fractures in a military population are in the femoral neck.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Femoral neck stress fractures (FNSFs) are rare injuries that often result in delayed diagnosis due to initial symptoms being overlooked [ 1 ]. They represent approximately 1%-2% of all femoral neck fractures, 3%-5% of all stress fractures, and account for about 3% of sport-related events [ 2 , 3 ]. FNSFs demonstrate a bimodal distribution, affecting both a younger, active demographic and an older population with potentially compromised bone quality or impaired bone repair mechanisms [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…FNSFs demonstrate a bimodal distribution, affecting both a younger, active demographic and an older population with potentially compromised bone quality or impaired bone repair mechanisms [ 4 ]. In the younger cohort, FNSFs are mainly observed among military personnel and high-performing athletes, commonly linked with a rapid increase in physical activity and endurance exercise [ 1 , 2 , 5 - 7 ].…”
Section: Introductionmentioning
confidence: 99%